Designing safer working interventions through a literature review using a mechanisms-based approach. (December 2019) - Pilbeam, Colin; Denyer, David; Doherty, Noeleen; Davidson, Ross
Highlights: Development of 5 design propositions to reduce accidents and injuries. Development of 5 design propositions to change safety behaviours. Investigation of the mechanisms that underpin safety practices to create safety outcomes. Abstract: The explanation for what safety interventions work in any particular circumstance remains elusive, resulting in many work-related fatalities and injuries every year. We propose a shift in perspective from a preoccupation with safety interventions and their effects to an elucidation of the generative mechanisms underpinning safety and its contiguous context. Using an analytical framework based on contexts, interventions, mechanisms and outcomes (CIMO) we were able to review 43 empirical studies of safety interventions deployed by leaders in organizations. This motivated the development of 10 design propositions; 5 related to accident and injury reduction and 5 to changing safety behaviours. Greater understanding of the mechanisms by which interventions exert their effects will lead to the design of more context appropriate safety interventions thereby enhancing individual and organizational safety in the future and the development of evidence-based safety.